Agenesis of the left hepatic lobe undergoing laparoscopic hepatectomy for hepatocellular carcinoma: a case report - Katsunori Matsushita; Kunihito Gotoh; Hidetoshi Eguchi; Yoshihumi Iwagami; Daisaku Yamada; Tadafumi Asaoka; Takehiro Noda; Hiroshi Wada; Koichi Kawamoto; Yuichiro Doki; Masaki Mori (Surgical Case Reports)
Abstract Background Agenesis of the left hepatic lobe is a rare anomaly. It is defined as the absence of liver tissue to the left of the gallbladder fossa. Additionally, agenesis of the left hepatic lobe accompanied by hepatocellular carcinoma is quite rare. We experienced the case of a patient with agenesis of the left hepatic lobe, undergoing laparoscopic hepatectomy for HCC. Case presentation A 79-year-old man was referred to our department with epigastralgia. Abdominal computed tomography revealed agenesis of the left hepatic lobe, accompanied by hepatocellular carcinoma in segments 7 and 8. He underwent laparoscopic partial hepatectomy of segments 7 and 8. The operative findings revealed complete agenesis of the liver to the left of the falciform ligament. The patient had a favorable clinical course without liver dysfunction or any complications. Conclusions We experienced a case with agenesis of the left hepatic lobe undergoing laparoscopic hepatectomy for HCC. Awareness of such anomaly is important for surgeons to avoid postoperative complications.